PENINGKATAN HASIL BELAJAR IPS TERPADU DENGAN MODEL PEMBELAJARAN KOOPERATIF MENCARAI PASANGAN (MAKE A MATCH) PADA SISWA KELAS VIII 2B DI SMP ISLAM AL-MUHSISNIN RIMBA MELINTANG ROKAN HILIR - Julina '; Henny Indrawati; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The learning model looking for a partner (make a match), was one technique of learning in which students find a partner while learning about a topic in a pleasant atmosphere in. The purpose of this study was to determine the improvement of learning outcomes IPS 2B VIII class integrated learning model looking couple (make a match) in SMP Islam Al-Muhsisnin transverse Rimba Rokan Hilir. The sample used is class VIII SMP Islam Al-2B Muhsisnin Rimba Rokan Hilir transverse half of the whole, while the number of students in class VIII 2B as many as 20 people. Data obtained using observation techniques. While data analysis techniques used are: analysis of the activity of teachers and students and the impact of the implementation of the action on student learning outcomes. From the results of data analysis that has been done shows cooperative learning model of finding a partner (make a match) can improve learning outcomes IPS 2B eighth grade students at SMP Islam Al-Muhsisnin transverse Rimba Rokan Hilir. From these results it is expected that the school, paying attention to cooperative learning model of finding a partner (make a match) that is used by the teacher in the learning process for the cooperative learning model looking couple (make a match) to improve learning outcomes. If the result of learning increases, the quality of schools also increased.Keywords: make a match Learning Method , learning outcomes